Neutrophil‐to‐lymphocyte ratio correlates with proinflammatory neutrophils and predicts death in low model for end‐stage liver disease patients with cirrhosis. Issue 2 (February 2017) - Kalra, Avash; Wedd, Joel P.; Bambha, Kiran M.; Gralla, Jane; Golden‐Mason, Lucy; Collins, Christine; Rosen, Hugo R.; Biggins, Scott W.
Abstract : The Model for End‐Stage Liver Disease (MELD) score has reduced accuracy for liver transplantation (LT) wait‐list mortality when MELD ≤ 20. Neutrophil‐to‐lymphocyte ratio (NLR) is a biomarker associated with systemic inflammation and may predict cirrhotic decompensation and death. We aimed to evaluate the prognostic utility of high NLR (≥4) for liver‐related death among low MELD patients listed for LT, controlling for stage of cirrhosis. In a nested case‐control study of cirrhotic adults awaiting LT (February 2002 to May 2011), cases were LT candidates with a liver‐related death and MELD ≤ 20 within 90 days of death. Controls were similar LT candidates who were alive for ≥90 days after LT listing. NLR and other covariates were assessed at the date of lowest MELD, within 90 days of death for cases and within 90 days after listing for controls. There were 41 cases and 66 controls; MELD scores were similar. NLR 25th, 50th, 75th percentile cutoffs were 1.9, 3.1, and 6.8. NLR was ≥ 4 in 25/41 (61%) cases and in 17/66 (26%) controls. In univariate analysis, NLR (continuous ≥ 1.9,  ≥ 4,  ≥ 6.8), increasing cirrhosis stage, jaundice, encephalopathy, serum sodium, and albumin and nonselective beta‐blocker use were significantly ( P  < 0.01) associated with liver‐related death. In multivariate analysis, NLR of ≥1.9,  ≥ 4,  ≥ 6.8 were each associated with liver‐related death. Furthermore, we found that NLR correlated with the frequency of circulating low‐density granulocytes, previously identified as displaying proinflammatory properties, as well as monocytes. In conclusion, elevated NLR is associated with liver‐related death, independent of MELD and cirrhosis stage. High NLR may aid in determining risk for cirrhotic decompensation, need for increased monitoring, and urgency for expedited LT in candidates with low MELD. Liver Transplantation 23 155–165 2017 AASLD